Pengaruh Kebiasaan Membaca Buku dan Kecerdasan Emosional terhadap Prestasi Belajar Bahasa Indonesia - Muhammad Khalidin (EduInovasi: Journal of Basic Educational Studies, 2021)
The study aims to analyze and test the validity of the hypothesis regarding the effect of Reading Books and Emotional Intelligence on Indonesian Language Learning Achievement of students. The research hypothesis tested includes: 1) Effect of Book Reading Habits on Students' Indonesian Language Learning Achievement. 2) Effect of Emotional Intelligence on Students' Indonesian Language Learning Achievement. 3) Interactive Influence on the Habit of Reading Books and Emotional Intelligence on Students' Indonesian Learning Achievement. The research was conducted by survey method with correlational techniques. The population used in this study is private vocational school students in Depok city. The study sample was 52 students. The results of the study: 1) There is a significant influence on the habit of reading books and emotional intelligence together on the learning achievement of Indonesian students of Depok Vocational High Schools. This can be proven by the Sig. 0.013 <0.05, and Fh = 4.786. the independent variables of reading habits and emotional intelligence together contribute 16.3% to the variation in the achievement of learning Indonesian. 2) There is a significant influence on the habit of reading books on the learning achievement of Indonesian language students of private vocational schools in Depok. This can be proven by the value of Sig.0,010 <0,05 and th = 2,697. 3) There is a significant influence of emotional intelligence together on the learning achievement of Indonesian students of Depok Private Vocational Schools. This can be proven by the Sig. 0.006 <0.05 and th = -2.864.